USE OF PROCESS VACCINE HAIRS OF ENZYMATIC PELAMBRE OF CURTIEMBRES IN THE LEAD REMOVAL - Palomino Amorína, Carmen Carola (2016)
In this study, waste hairs of the enzymatic unhairing process (PPE) of tannery were used as adsorbents to remove lead of a solution. Waste hairs were treated with acid hydrolysis and used in the type batch adsorption experiments, to be examined the effect of pH on the adsorption and also to investigate the mechanism of adsorption for which studies adsorption isotherms and the adsorption kinetics of Pb (II) were performed on treated hairs. The results showed that adsorption of Pb (II) was pH dependent with the optimum pH of 7. Isotherm studies showed that experimental data match the pattern of the Langmuir isotherm for the case of treated hairs of the enzymatic unhairing process (PTPE). The maximum adsorption capacity was 321.20 mg Pb (II)/g of bioadsobent (PTPE). The kinetic studies showed that the reaction model of pseudo-second order best describes the adsorption process. Finally, the study showed that residues of hairs of the enzymatic unhairing process can be used as effective adsorbents for the removal of lead (II).